Analysis of a Transportation System with Correlated Network Intersections: A Case Study for a Central Urban City With High Seasonal Fluctuation Trends - Tayan, Omar; Alginahi, Yasser M.; M. Nomani, Kabir; Al Binali, Abdullah M. (IEEE, 2017)
Intelligent transportation systems (ITSs) providing efficient road-transportation strategies have recently become a very active research area. Efficient transportation of visitors to/from highly congested sites is one of the most important challenges addressed by ITS. A transportation-system analysis is presented here and is applied on an urban city ring road network that encompasses a major attraction site characterized by correlated network-intersections and large vehicle-pedestrian movement conflicts. The presented model analysis first examines the influences exerted by network-correlations at intersection-points, and second, presents case-study evacuation scenarios examined under varying circumstances and flow-requirements within each segment of the modeled network. The significance of this paper is clearly evident in emergency/evacuation scenarios or in design considerations in which the influence of correlated network-intersections must be known beforehand. As a main contribution, a mathematical model was developed with simulations evaluating the current system using real-life data as statistical input to our model. Results had demonstrated the counter-propagation effect between adjacent intersections along the ring road of an urban congested city. Furthermore, the study modeled and investigated two emergency-evacuation scenarios within chosen segments at road network sites entering and exiting the central area in order to demonstrate how efficient evacuation can be conducted during an emergency scenario. It is expected that the results of this model can also be extended and applied for evacuation analyses for other sites with similar practical conditions or in other congested cities in which correlated intersections have a significant presence that must be included in the real-life analysis of a transportation system.